(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2010)
Keywords: salmonella; abscess; neck DOI: 10.3329/jcmcta.v20i2.5628 Journal of Chittagong Medical College Teachers’ Association 2009: 20(2):51-52